Jenis Tumbuhan Obat Yang Dikonsumsi Monyet Ekor Panjang (Macaca fascicularis) Di Goa Kreo - Amanda Irmayanti; Anisa Mayada Nuraini; Desti Nur Anggraini; Lussana Rossita Dewi (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Kreo Cave is one of Macaca fascicularis habitats in Central Java Province. Kreo Cave has been used as a natural tourist spot in the city of Semarang since 2014. One of the attractions for visitors is the presence of monkeys in the area, especially around the cave. Macaca fascicularis is a type of non-human primate whose distribution is very wide. Macaca fascicularis have an important role for an area, one of which is as a eater of fruits and seeds found in the area, thus helping in the distribution of seeds in order to maintain the balance of nature. The purpose of this research is to describe the types of food eaten and can be used as medicine for Macaca fascicularis. The results showed that Macaca fascicularis in the Kreo Cave Tourism Area ate several plants in the area such as Tamarindus indica, Musa paradisiaca, Psidium guajava, Mangifera indica, Nephelium lappaceum, Leucaena leucocephala, and Morinda citrifolia. When visitors brought bananas, several monkeys came closer and then the visitors threw them at the monkeys. The faster monkey will get the bananas. After the banana is in his hand, Macaca fascicularis takes him to a quiet place or away from their friends.